Odpowiedzi

2010-03-17T21:26:41+01:00
A)
x/(4x-1)=1
x=4x+1
5x=1
x=0,2

b)
5/(2x+1)=3/(2x-z)
5*(2x-1)=3*(2x+1)
10x-5=6x+3
4x=8
x=2

c)
x/(x+1)+x/(x-2)=2
x+(x^2+x)/(x-2)=2x+2
x(x-2)+x^2+x=(2x+2)*(x-2)
x^2-2x+x^2+x=2x^2-2x+2x-4
2x^2-x=2x^2-4
x=4

d) to równanie jest rozwiązane deltą
(6/x)-[2/(x-1)]=1
6-[2x/(x-1)]=x
6x-6-2x=x^2-x
4x-6=x^2-x
5x-6=x^2
-x^2+5x-6=0

∆ (delta)=b^-4ac
a=-1
b=5
c=-6
∆=5^2-4*(-1)*(-6)
∆=1

x jeden = (-b+√∆)/2a
x dwa = (-b-√∆)/2a

x jeden = (-5+1)/(-2)=-4/-2=2
x dwa = (-5-1)/-2=-6/-2=3

to równanie ma dwa rozwiązania: 2 i 3